Beyond the Hive Mind: Leveraging the Artificial Bee Colony Model for Collaborative Learning in English Language Teaching - Venosha Ravana; Thilip Kumar Moorthy; Sarala Thulasi Palpanadan (Development in Language Studies, 2024)
Innovative teaching strategies that support a variety of learning styles and promote productive collaboration are desperately needed, as the number of ESL students enrolled in university courses rises. This study conceptualizes the integration of the Artificial Bee Colony (ABC) model with constructivist principles to enhance collaborative learning in English Language Teaching (ELT). The expected outcomes from the proposed Design and Development Research (DDR) study include improved group formation, enhanced student engagement and participation, more effective task allocation, and better academic performance.